A new hope for conserving the disjunct population of the Sierra Madre Sparrow Xenospiza baileyi: population size and new breeding localities in the Sierra Madre Occidental, Mexico. (29th June 2023) - Aguirre-Calderón, Carlos Enrique; Sánchez-Escalera, Armando; Ruvalcaba-Ortega, Irene; Aguirre-Calderón, Cristóbal Gerardo; Vargas-Larreta, Benedicto; Hernández, Francisco J.; Canales-del-Castillo, Ricardo; Gonzalez Rojas, Jose Ignacio
Summary: The Sierra Madre Sparrow Xenospiza baileyi is an endangered Mexican endemic and a bunchgrassland specialist with a disjunct range: a relatively larger population in the south-eastern Trans-Mexican Volcanic Belt, and a smaller and poorly studied population in the Sierra Madre Occidental. In the latter, known distribution and abundance consists of four localities with a maximum of 28 individuals recorded in one of them. We surveyed the Sierra Madre Sparrow in 30 sites with suitable habitat, meadows or "bajíos" with bunchgrasses, in the municipalities of Durango, Pueblo Nuevo, San Dimas, and Canatlán in the Sierra Madre Occidental of Durango. We detected a total of 193 individuals in nine (30%) of the sites (392 ha), conducting intensive searches throughout them. Bunchgrasses in confirmed meadows were composed mainly of Muhlenbergia macroura, M. rigida, M. speciosa, M. rigens, and Piptochaetium fimbriatum. Total bunchgrass area within a meadow was a significant positive predictor of the Sierra Madre Sparrow presence, while total meadow area was not a significant predictor of its abundance. Seven of the confirmed localities were previously unknown, and two of them harboured 55% of the observed individuals: Ex Hacienda Coyotes (Pueblo Nuevo) and La Lobera (San Dimas). The estimated population size is at least four times higher than any previous record (28) or suggested (40–50) for the Sierra Madre Occidental and raises an opportunity and a challenge for conserving this genetically distinct population of the Sierra Madre Sparrow in the region.